PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP VOLUME PENJUALAN IKAN ASIN PADA MASA “COVID 19” DI KECAMATAN LOSARI - Umama Sari; Hendri Sucipto; Yenny Ernitawati (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to analyze the effect of product quality and price on the sales volume of salted fish in the Aulia Putri company, Kecipir Village, Losari District, Brebes Regency. The population in this study was salted fish resellers at Aulia Putri Company. The sample in this study was 65 respondents. Data collection is carried out by distributing questionnaires or questionnaires to salted fish resellers at aulia putri company. This study used multiple linear regression analysis tools. The hypothesis was tested with the t test and the F test. Test results showed that (1) the quality of the product had a positive and significant effect on the sales volume of salted fish partially with a calculated t value result of 3.752 > t table 1.668; (2) the price has a positive and significant effect and is significant to the sales volume of salted fish partially with a calculated t value result of 3,488 > t table 1,668; (3) product quality and price simultaneously positively affect the sales volume of salted fish in aulia putri company with F count 7,091 > F table 3.14 with a significant level of 0.000 < 0.05.